THE ROLE OF CHEMICAL TECHNOLOGIES IN THE PROCESSING OF ECOLOGICAL DOMESTIC WASTE (Academia Science Repository, 2023)
There are two different approaches to technical innovation in chemistry. The first is that new technologies and processes reduce the cost of eliminating sources of pollution to a minimum level, and the second is that new technologies (the right way to approach this issue) ensure the radical elimination of the cause of actual or potential chemical problems.